High prevalence and intensity of Stephanurus dentatus in a population of wild boar (Sus scrofa) in south western Spain. (October 2018) - Moratal, S.; Ruíz de Ybáñez, R.; Barroso, P.; Granados, J.E.; Höfle, U.; Martínez-Carrasco, C.; Acevedo, P.; Vicente, J.
Highlights: The presence of the urinary tract nematode parasite Stephanurus dentatus was investigated in wild boar in Spain. S. dentatus was detected in wild boar in Doñana National Park, but not in three other areas in central and south Spain. The focus of infestation of wild boar with S. dentatus in Doñana National Park had a high prevalence and a high intensity. The prevalence of S. dentatus was lower in juvenile wild boar than in subadult and adult wild boar. Doñana National Park constitutes a promising scenario for future epidemiological studies on S. dentatus in wild boar. Abstract: In the period from October 2016 to February 2017, the urinary tracts of 390 wild boar ( Sus scrofa ) from four areas of south central Spain (102 from Doñana National Park; 150 from Sierra Morena and the Toledo Mountains; 84 from Sierra Nevada; 54 from Sierra de Cazorla, Segura y Las Villas Natural Park) were examined for the presence of adult specimens of Stephanurus dentatus (Nematoda: Strongyloidea). This parasite was only detected in the wild boar population of Doñana National Park, with high prevalence (76.5 ± 4.2%; 78/102), mean intensity (43.2 ± 4.4) and mean abundance (33.1 ± 3.8). Juvenile wild boar had significantly lower prevalence and abundance than subadult and adult wild boar. The intensity of infestation was significantly higher in male than in female wild boar. The detection of a focus of S. dentatus infestation in the wild boar population in Doñana National Park will provide further opportunities for understanding the epidemiology of this parasite.